Enhancing communication and social engagement among clinicians and research teams to improve reliability of research recruitment - Chang, Joyce C (BMJ Open Qual, 2019)
The success of rare disease research relies heavily on robust partnerships with clinicians to help identify new patients and collect samples. Many studies for paediatric rheumatic diseases requiring pretreatment samples have suffered from slow enrolment rates due to the low incidence of disease and relative urgency to treat. Therefore, timely identification of all potentially eligible patients is crucial. The objective of this project was to apply quality improvement methods to increase the frequency and timeliness of identification of eligible patients with new paediatric rheumatic diagnoses to approach for research studies. A retrospective chart review was undertaken in our paediatric rheumatology clinic to measure the number of eligible patients identified for potential research recruitment between missed recruitment opportunities. Improvement methodology was used to integrate standardised communication between clinicians and the research team into clinic workflow, to leverage social feedback as positive reinforcement for good communication and to measure change in response to the interventions. The number of eligible patients identified between missed recruitment opportunities increased from every 0–1 patient to every 14 patients during the project period, corresponding to an increase in the overall identification rate from 32% to 91% of all eligible patients. Quality improvement methods can be used to successfully integrate research recruitment into routine clinical care and accelerate advances necessary to improve health outcomes.